Factors and Strategies for The Development of Buffalo Production in Aceh Barat District - Anisa Yuliandha; Nevy Diana Hanafi; Sri Fajar Ayu (RIRAI Publisher, 2024)
This study analyzes what factors affect buffalo production in Aceh Barat District. Analyze what factors are more dominant in influencing buffalo production in Aceh Barat District. Determining the strategy for buffalo development in Aceh Barat District This research was conducted in Aceh Barat District from April to August 2023 with a sample of 90 farmers spread across three districts in Aceh Barat. The data analysis used was to use liner regression coo Douglas analysis to see the factors affecting. The results of multiple regression analysis can be seen that the factors of seeds, labor, cage area, total feed have a real effect on buffalo livestock production in Aceh Barat.